Do the qualifications of vocational teachers make a difference to their teaching?. Issue 1 (2nd January 2023) - Smith, Erica; Tuck, Jacqueline
ABSTRACT: A survey of over 500 teachers and trainers in the Australian Vocational Education and Training (VET) sector was carried out to examine whether their teaching practices and approaches varied with their qualification levels. The survey, carried out with teachers and trainers from different types of training providers – public and private – formed a major part of a larger research project on the topic. The project was carried out because of an overall decline in the qualification levels of the VET teaching workforce over a 20-year period, and national debate on the appropriate qualification level. Analysis of the survey results showed that those with pedagogical qualifications above the regulatory minimum were more confident overall, and were more able to deal with the demands of different teaching contexts and of diverse learner groups. Teachers with higher level qualifications also reported, in qualitative questions, specific gains from their qualifications. They were also more likely to undertake professional development, challenging an often-cited view that professional development activities can compensate for lower qualification levels. The findings have implications for policy development in Australia and elsewhere.